Comparative study of Ag, Sn or Zn doped TiO2 thin films for photocatalytic degradation of methylene blue and methyl orange. (6th September 2019) - Tariq, Muhammad Kamran; Riaz, Adeel; Khan, Ramsha; Wajid, Ahsan; Haq, Hamza-ul; Javed, Sofia; Akram, Muhammad Aftab; Islam, Mohammad
Abstract: Nanocrystalline titania (TiO2 ) films with high optical transmittance and appropriate type and level of metal dopants offer promise for use in photocatalysis and environmental remediation purposes. In this study, a facile, cost-efficient sol-gel reflux synthesis route was devised to obtain smooth, nanocrystalline anatase TiO2 thin films doped with silver (Ag), tin (Sn) or zinc (Zn) with up to 5 mole percent. The microstructure, surface morphology and phase composition were determined using scanning electron microscope, atomic force microscope and x-ray diffraction techniques. The films were found to be nanocrystalline with average crystallite size of the order of ∼11 nm. Upon Ag or Sn doping, the films became superhydrophilic due to generation of surface defects and enhanced absorption via incident light scattering. The low extinction coefficient confirmed low surface roughness and uniform dispersion of the metal dopants into the TiO2 lattice. There was a decrease in the refractive index values of the Zn-doped films. The band gap values, as computed using Tauc plots, indicated a maximum reduction from 3.66 eV for the updoped TiO2 to 3.25 eV for Ag-doped TiO2 film. When assessed for photocatalytic degradation of methylene blue (MB) and methyl orange (MO), all the films were found to follow pseudo first-order kinetics in accordance with the Langmuir-Hinshelwood model. The apparent rate constant values were found to increase by 2 to 3 fold (4.30 × 10 −3 s –1 for MB; 5.34 × 10 −3 s –1 for MO) upon doping with 5 mole percent ZnO, presumably due to dual role of Zn as a reductant causing Ti 3+ formation and a stabilizer of the oxygen vacancies.